2018
DOI: 10.4062/biomolther.2017.179
|View full text |Cite
|
Sign up to set email alerts
|

The Pentose Phosphate Pathway as a Potential Target for Cancer Therapy

Abstract: During cancer progression, cancer cells are repeatedly exposed to metabolic stress conditions in a resource-limited environment which they must escape. Increasing evidence indicates the importance of nicotinamide adenine dinucleotide phosphate (NADPH) homeostasis in the survival of cancer cells under metabolic stress conditions, such as metabolic resource limitation and therapeutic intervention. NADPH is essential for scavenging of reactive oxygen species (ROS) mainly derived from oxidative phosphorylation req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
111
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 61 publications
4
111
0
Order By: Relevance
“…**P < 0.01 compared to untreated cells3.2 | Effect of Nrf2 on pentose phosphate pathway in breast cancer cellsPentose phosphate pathway (PPP) is a major glucose metabolism pathway, which is fundamental in cancer growth and metastasis 19. Nrf2-specific shRNA or overexpression of Nrf2 caused a decrease in Nrf2 mRNA and protein expression in MCF-7 and MDA-MB-231 cells.…”
mentioning
confidence: 99%
“…**P < 0.01 compared to untreated cells3.2 | Effect of Nrf2 on pentose phosphate pathway in breast cancer cellsPentose phosphate pathway (PPP) is a major glucose metabolism pathway, which is fundamental in cancer growth and metastasis 19. Nrf2-specific shRNA or overexpression of Nrf2 caused a decrease in Nrf2 mRNA and protein expression in MCF-7 and MDA-MB-231 cells.…”
mentioning
confidence: 99%
“…Therefore, a decreased activity of this pathway will impair proliferation and defence against oxidative stress, and it has been discussed that the PPP could be in fact a potential target for cancer therapy. 32 In previous investigations, the anti-neoplastic of carnosine was shown to be associated with decreased ATP production. However, there have been different reports either pointing towards an effect on glycolysis, mitochondrial respiration or on both, depending on the cell type investigated.…”
Section: Discussionmentioning
confidence: 93%
“…The PPP is especially important for tumour cells as it provides nucleotides for nucleic acid synthesis and NADPH required for fatty acid synthesis and scavenging of reactive oxygen species (for review see). Therefore, a decreased activity of this pathway will impair proliferation and defence against oxidative stress, and it has been discussed that the PPP could be in fact a potential target for cancer therapy …”
Section: Discussionmentioning
confidence: 99%
“…One major mechanism for enhancing ROS levels in cancer cells occurs via a feedback amplification loop involving ROS‐mediated increase in cytosolic NADPH production. Thus, metabolic profiling and other studies described below have shown for many cancer cell types that glycolysis is partly shunted via Glc6PDH into the oxidative PPP branch leading to this being proposed as a target for cancer therapy . In fact, studies of human skin cells revealed that hypoxia increased ROS (such as H 2 O 2 ) directly and rapidly increased the activity of the PPP as a first‐line defense against ensuing oxidative stress and which was alleviated via increased NADPH production essential to prevent against oxidative damage .…”
Section: Introductionmentioning
confidence: 98%
“…More importantly, PPP activation also serves the additional purpose of ensuring a continuing NADPH production required for TrxR1 function as a critical antioxidant system in advanced stage cancer cells and CSCs . The mechanisms of metabolic reprogramming in metastatic cancer cells and roles for mut‐p53/ nuclear respiratory factor 2 (NRF2) and HIF‐1, as well as the importance of the NADPH/TrxR axis in advanced stage cancer cell metabolism have been previously reviewed and are not further discussed here .…”
Section: Introductionmentioning
confidence: 99%